Power optimisation of small scale SPV array using field programmable reconfiguration topology for dynamic non-uniform illumination state - Prakash, Surya; Rastogi, Swati; Gupte, Shaunak M; Duttagupta, Siddhartha P (Journal of engineering (Stevenage, England), 2020)
The power output of the solar-photovoltaic (SPV) array is affected significantly by non-uniformly incident solar radiation. Such non-uniform illumination (NUI) condition(s) occur due to shadows of terrestrial structures (like buildings, trees, etc.) or through the creation of hotspot(s) in the contribution of moisture-dust accumulation, bird droppings, etc. which are predictable in nature. Furthermore, projected images of cloud(s) also cause NUI impact which is unpredictable and is/are subject to variables such as 3-D cloud coverage, cloud density, wind speed, etc. Literature also affirms that SPV array architecture plays a critical role in NUI effect mitigation. The novelty of this paper is the introduction of switching network system with the flexibility in the arrangement of the SPV panel series–parallel connections as per solar light intensity, NUI pattern, and data obtained from panel's peripheral light sensors. The field programmable reconfiguration strategy proposed here will get the power vs voltage curve and current vs voltage curve to identify maximum power-point. Multiple NUI patterns are simulated in MATLAB with variance in SPV array matrix and peripheral sensor matrix. This proposed reconfiguration method is cost-effective and includes embedded devices that could be widely implemented for domestic as well as commercial applications with the nested sub-array scheme.